The mirror in the landscape: testing boundaries of the reflexive documentary film mode - Bothma, Bianca (My University, 2014)
The following research report about documentary filmmaking theory takes as its starting point that the voice in the filmmaker is present in films though devices of the reflexive mode. This mode of documentary has been widely described as a form used in films to make a statement. By raising the viewers' awareness of its constructs through stylistic devices and techniques, the film surfaces the politics of representation and acknowledges its subjective quality. However, not all reflexive devices are used to achieve the same ends and different techniques can have a number of results, which add layers to narrative. The popular text by Nichols, Representing Reality, Issues and Concepts in Documentary, (1997) claims that there are several different kinds of reflexivity and that they can be separated into two types, political and formal. This classifif ation is useful for analysis purposes but these kinds often are difficult to separate as the reflexive documentary often converges a variety of techniques. This report focuses on how different kinds of reflexivity allow for the presence of several dimensions of one filmmaker, which results in: in a voice that has a plurality of objectives; and new forms of the reflexive documentary film. In addition, the argument is also made for a new class of reflexivity, that landscape can be employed as a reflexive device to reveal the internal psychological dimension of the filmmaker. As a case study, the popular films of Werner Herzog are read as instances, which successfully converge the different kinds of reflexivity. A formal analysis on two films by German filmmaker Werner Herzog, Grizzly Man (2005) and Encounters at the End of the World (2007) includes a description of how the filmmaker employs landscape as a reflexive device. This is then further discussed in terms of how the two films influenced the film made for this project, Extraction with reflections on how theory was implemented and what was learnt from the process. The conclusion of the report includes reflections on and insights from testing the boundaries of the reflexive mode with hybrid reflexivity and the practice of employing landscape as a reflexive landscape.
Thesis (M.A)--University of the Witwatersrand, Faculty of Humanities, Film and Television, 2013